Pyrolysis and Gasification of Cotton Scrap Materials as a Municipal Solid Waste Material - Gulen, J.; Arslan, H. (TAYLOR & FRANCIS INC, 2009)
Fixed bed pyrolysis experiments have been conducted on waste cotton scrap materials for converting into fuel form. The effect of temperature on the pyrolysis experiments has been investigated at the temperatures of 250 degrees C, 350 degrees C, 500 degrees C, 600 degrees C, 700 degrees C, 800 degrees C, and 900 degrees C. The maximum liquid amount (30%) was obtained at 500 degrees C with 700 cm(3)/min N(2) sweep gas flow rate of 5 degrees C/min heating rate. The pyrolytic liquid was characterized by elementel analysis and chromatographic technique. First, this liquid was fractionated into n-pentane soluble and insoluble compounds (asphaltenes). Pentane soluble was then solvent fractionated into n-pentane, toluene, and methanol subfractions by fractionated column chromatography. The chemical characterization had shown that the pyrolytic liquid obtained from cotton scrap materials was quite similar to petroleum fuels.
Keywords: cotton; gasification; pyrolysis; temperature; waste material; FIXED-BED PYROLYSIS; CHARCOAL; YIELDS; Energy & Fuels; Engineering; Environmental Sciences & Ecology